ROZWIĄZANIE DAJCIE TYLKO DZIŚ !
BO MAM TO NA JUTRO
Usuń nawiasy i zredukuj wyrazy podobne:
a){3a+a2-[(a-3a2+2b)]}=
2- kwadratowych
a kwadrat
3a kwadrat
b)3x2-[(xy+y2-2x)-2x2+2xy-2x)]=
3x kwadrat
y kwadrat
2x kwadrat
2 - kwadratowych
c)-[3mk-(k2-2mk+m2)]-(m2-5mk-2k2)=
2 -kwadratowych
k kwadrat
m kwadrat
m kwadrat
2k kwadrat

1

Odpowiedzi

2010-03-25T13:44:39+01:00
A)
{3a+a2-[(a-3a2+2b)]}=
3a+a²-[a-3a²+2b] =
3a+a²-a+3a²-2b =
7a²-a-2b


b)
3x2-[(xy+y2-2x)-2x2+2xy-2x)]=
3x²-[xy+y²-2x-2x²+2xy-2x] =
3x²-xy-y²+2x+2x²-2xy+2x =
5x²-3xy-y²+4x


c)
-[3mk-(k2-2mk+m2)]-(m2-5mk-2k2)=
-[3mk-k²+2mk+m²]-m²+5mk+2k² =
-3mk+k²-2mk-m²-m²+5mk+2k² =
3k²-2m²